Molecular Characterization of Cronobacter sakazakii Strains Isolated from Powdered Milk - Ondrej Holý; Julio Parra-Flores; Sarah Lepuschitz; María Paula Alarcón-Lavín; Ariadnna Cruz-Córdova; Juan Xicohtencatl-Cortes; Jetsi Mancilla-Rojano; Werner Ruppitsch; Stephen Forsythe (Foods, 2020)
Cronobacter spp. are opportunistic pathogens of the Enterobacteriaceae family. The organism causes infections in all age groups, but the most serious cases occur in outbreaks related to neonates with meningitis and necrotizing enterocolitis. The objective was to determine the in silico and in vitro putative virulence factors of six Cronobacter sakazakii strains isolated from powdered milk (PM) in the Czech Republic. Strains were identified by MALDI-TOF MS and whole-genome sequencing (WGS). Virulence and resistance genes were detected with the Ridom SeqSphere+ software task template and the Comprehensive Antibiotic Resistance Database (CARD) platform. Adherence and invasion ability were performed using the mouse neuroblastoma (N1E-115 ATCCCRL-2263) cell line. The CRISPR-Cas system was searched with CRISPRCasFinder. Core genome MLST identified four different sequence types (ST1, ST145, ST245, and ST297) in six isolates. Strains 13755-1B and 1847 were able to adhere in 2.2 and 3.2 × 106 CFU/mL, while 0.00073% invasion frequency was detected only in strain 1847. Both strains 13755-1B and 1847 were positive for three (50.0%) and four virulence genes, respectively. The cpa gene was not detected. Twenty-eight genes were detected by WGS and grouped as flagellar or outer membrane proteins, chemotaxis, hemolysins, and invasion, plasminogen activator, colonization, transcriptional regulator, and survival in macrophages. The colistin-resistance-encoding mcr-9.1 and cephalothin-resis-encoding blaCSA genes and IncFII(pECLA) and IncFIB(pCTU3) plasmids were detected. All strains exhibited CRISPR matrices and four of them two type I-E and I-F matrices. Combined molecular methodologies improve Cronobacter spp. decision-making for health authorities to protect the population.